Guillain-Barré Syndrome: A Comprehensive Review of Pathophysiology, Diagnosis, and Advances in Management - Harsh Vardhan Katariya; Shivkumar Patel; Kashish Parvani; Mohit Buddhadev; S P Srinivas Nayak (Asian Journal of Pharmaceutical Research and Development, 2025)
Guillain-Barre syndrome (GBS) is an uncommon autoimmune disease-almost in all hysterical cases-paralysis in the strong muscle group and the progressive muscle weakness are the cardinal features associated with peripheral nerve destruction. The review aims at presenting all-rounded discussions on the latest understanding of pathophysiology, diagnostic strategies, and remedies in the recent management of GBS. The pathogenic events include immune-mediated demyelination and axonal degeneration, often provoked by infections. The clinical manifestations span from minor symptoms, progressing to a high-risk clinical condition defined by respiratory failure, implying the need for an early diagnosis and therapy. Improvements in the diagnosis modalities of electrophysiological studies and cerebrospinal fluid analysis have favored early detection-colon or reclassification of subtypes. Treatment modalities include immune modulatory therapies with intravenous immunoglobulin (IVIG) and plasma exchange (PLEX) treatments, but emerging treatments are conveying new hope toward better outcomes. With this background also include recent advances in aspects of supportive treatment, prognostic indicators, and ongoing research on novel classes of therapeutic agents. However, great strides have been made to improve and individual customize treatment strategies, and a greater understanding of long-term outcomes is achieved but remains work to be done. The article presents as a testimony to early recognition, multidisciplinary approach to management, and enthusiasm for continuing to research human subject areas to improve prognosis and quality of life further.